The Routledge handbook of disability and sexuality - Shuttleworth, Russell; Mona, Linda (Routledge, 2021)
This handbook provides a much-needed holistic overview of disability and sexuality research andscholarship. With authors from a wide range of disciplines and representing a diversity of nationalities, it provides a multi-perspectival view that fully captures the diversity of issues and outlooks. Organised into six parts, the contributors explore long-standing issues such as the psychological, interpersonal, social, political and cultural barriers to sexual access that idsabled people face and their struggle for sexual rights and participation. The volume also engages issues that have been on the periphery of the discourse, such as sexual accomodations and support aimed at facilitating disabled people's sexual well-being; the socio-sexual tensions confronting disabled people with intersecting stigmatised identities such as LGBTBI or asexual; and the sexual concerns of disabled people in the Global South. It interrogates disability and sexuality from diverse perspectives, from more traditional psychological and sociological models, to various subversive and post-theoretical perspectives and queer theory. This handbook examines the cutting-edge, and sometimes ethically contentious, concerns that have been repressed in the field. With current, international and comprehensive content, this book is essential reading for students, academics and researchers in the areas of disability, gender and sexuality, as well as applied disciplines such as healthcare pratictionners, counsellors, psychology trainees and social workers.
Le texte Santinele Martino, A. et Fudge Schormans, A. (2021). Theoretical developments: Queer theory meets crip theory a été donné en lecture au cours SEX1920
Keywords: EDI; LGBTQIA2+; accessibilité; approches et analyses; capacitisme; care; corps; cours; discipline; histoire et politique; identités LGBTQIA2+; intersectionnalité; outils; ouvrages de références; premier cycle; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1911; sex1920; sexologie; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

The Oxford handbook of language and sexuality - Hall, Kira; Barrett, Rusty (Oxford University Press, 2018)
Disponible en ligne à https://academic.oup.com/edited-volume/42645?login=true Donné en lecture au cours LIN2685, King, Brian W. "Language and embodied sexuality", pp1-20.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; langage; lin2685; linguistique; outils; ouvrages de références; premier cycle; queer; ressource en ligne; sciences humaines; sexualité; sociolinguistique; thématiques

Arts visuels - Foucher Zarmanian, Charlotte (Encyclopédie critique du genre : corps, sexualité, rapports sociaux, 2016)
"Arts visuel" est l'un des soixante-six textes thématiques de cette encyclopédie explorent les reconfigurations en cours des études de genre. Trois axes transversaux organisent cette enquête collective: le corps, la sexualité, les rapports sociaux. Les inégalités liées au genre sont de plus en plus envisagées en relation avec celles liées à la classe sociale, la couleur de peau, l'apparence physique, la santé ou encore l'âge. Cette approche multidimensionnelle des rapports sociaux a transformé radicalement les manières de penser la domination au sein des recherches sur le genre. En analysant les concepts, les enquêtes empiriques et les débats caractéristiques de ces transformations saillantes, les contributrices et contributeurs de cet ouvrage dessinent une cartographie critique des études de genre en ce début de XXIe siècle.
Keywords: 1900-1999; 2000 à aujourd'hui; approches et analyses; arts visuels et médiatiques; corps; cours; discipline; encyclopédie; europe; fem1000; france; genre; histoire; identité sexuelle; identités LGBTQIA2+; intersectionnalité; occident; outils; premier cycle; recherche en milieux de pratique; ressource en ligne; régions géographiques; sciences humaines; sexualité; thématiques